PENYELESAIAN TINDAK PIDANA PENADAHAN DENGAN PRINSIP RESTORATIVE JUSTICE DALAM TAHAP PENYIDIKAN - Rudiyanto, Rudiyanto; Zeinudin, Moh.; Fithry, Abshoril (Jurnal Jendela Hukum, 2023)
The crime of detention can be resolved using the principles of Restorative Justice. Looking at the discussions above, it is clear that according to the legal rules restorative justice can be applied in criminal acts of detention as in Article 480 and Article 482 of the Criminal Code.